“And he wept over Jerusalem”: On possible sources of Francysk Skaryna’s engraving of prophet Jeremiah in Bivlia Ruska - Shutova, Olga (Knygotyra, 2023)
The article discusses the possibilities of understanding the woodcuts of Francysk Skaryna’s Bivlia ruska from the perspective of the intellectual ‘cosmos’ in the Renaissance Europe. We shall focus on the engraving “Jeremiah the prophet of the Lord weeps while looking at Jerusalem” (árámia púrr¼k7 g³dán6 pla+át6 glád3 na árusali, Скорина Ф. Книжка рекомая плачь Еремиинъ, hereinafter: The Book of Lamentations) putting it in the context of the iconography of this biblical character in the Renaissance. The article warns against ‘inscribing’ Skaryna’s image of Jeremiah in already-prepared schemes. Leaving open the solution of the possible visual sources of Skaryna’s engravings, we would like to avoid its traditional reading, based mainly on classifications, too often subjective and artificial. Our reading of Jeremiah is based on the study of his visual representations widespread in the Renaissance Europe in the late 15th and the early 16th centuries (Albrecht Dürer’s woodcut St. Anthony Reading from 1519; Hartmann Schedel’s Liber Chronicarum, 1493; Biblia vulgare istoriata, 1490, translated by N. Malermi; Biblij Czěská, w Benatkach tisstěná, 1506; Bernard von Breydenbach’s Sanctae peregrinationes, 1486; Werner Rolewinck’s Fasciculus temporum omnes antiquorum cronicas complectens, 1473/74 and its Venetian reprints by E. Ratdolf in the 1480s, etc.). The article emphasizes the importance to frame this iconography in the philosophical and aesthetical contexts of Francysk Skaryna’s epoch (by appealing to such sources as Dürer’s diaries, the works of Marsilio Ficino, quotations of F. Skaryna himself, etc.). We shall examine the plot, the characteristic features of Jerusalem landscape, architecture, religious symbols, and clothes represented at Jeremiah’s engraving in Bivlia ruska to seek the possible sources and inspirations of this engraving, while emphasizing its original character.